2021
DOI: 10.1002/cam4.3884
|View full text |Cite
|
Sign up to set email alerts
|

BACH1 promotes the progression of esophageal squamous cell carcinoma by inducing the epithelial–mesenchymal transition and angiogenesis

Abstract: Metastasis to regional lymph nodes or distal organs predicts the progression of the disease and poor prognosis in esophageal squamous cell carcinoma (ESCC). Previous studies demonstrated that BTB and CNC homology 1 (BACH1) participates in various types of tumor metastasis. However, the function of BACH1 in ESCC was rarely reported. The present study demonstrated that BACH1 protein was overexpressed in ESCC tissues compared with paired esophageal epithelial tissues according to immunohistochemical staining (IHC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 46 publications
5
17
0
Order By: Relevance
“…Zhao et al have identified BTB Domain and CNC Homolog 1 ( BACH1 ) TF as promoter of EMT in esophageal squamous cell carcinoma cells. They have shown that BACH1 directly binds to the promoter region of CDH2, SNAI2, Vimentin, and VEGFC genes and regulate their transcription [ 228 ]. BACH1 was further shown to induce EMT and promote pancreatic cancer metastasis (Sato et al, Cancer Res.…”
Section: Other Emt Tfsmentioning
confidence: 99%
“…Zhao et al have identified BTB Domain and CNC Homolog 1 ( BACH1 ) TF as promoter of EMT in esophageal squamous cell carcinoma cells. They have shown that BACH1 directly binds to the promoter region of CDH2, SNAI2, Vimentin, and VEGFC genes and regulate their transcription [ 228 ]. BACH1 was further shown to induce EMT and promote pancreatic cancer metastasis (Sato et al, Cancer Res.…”
Section: Other Emt Tfsmentioning
confidence: 99%
“…The results of in vitro assays also support the involvement of BACH1 in the metastatic properties of cancer cells. Invasion and migration activities of PDAC cells, esophageal cancer cells, colon cancer cells, and ovarian cancer cells in vitro are reduced upon BACH1 knockdown ( 79 , 80 , 81 , 82 , 83 , 84 ). When overexpressed in colon or ovarian cancer cells, BACH1 enhanced tumor growth in transplanted mice, but metastasis was not investigated ( 81 ).…”
Section: Functions Of Bach1 In Cancer Metastasismentioning
confidence: 99%
“…When overexpressed in colon or ovarian cancer cells, BACH1 enhanced tumor growth in transplanted mice, but metastasis was not investigated ( 81 ). An increased expression of BACH1 was shown to be correlated with a poorer prognosis of patients with breast, pancreatic, colorectal, ovarian, and esophageal cancers as well as glioblastoma ( 79 , 80 , 81 , 84 , 85 , 86 ). Taken together, these observations indicate that cancer cells acquire metastatic potential when the activity of BACH1 is increased.…”
Section: Functions Of Bach1 In Cancer Metastasismentioning
confidence: 99%
See 2 more Smart Citations